Controlled binding of organic guests by stimuli-responsive macrocycles. (12th May 2020) - Blanco-Gómez, Arturo; Cortón, Pablo; Barravecchia, Liliana; Neira, Iago; Pazos, Elena; Peinador, Carlos; García, Marcos D.
Abstract : Synthetic supramolecular chemistry pursues not only the construction of new matter, but also control over its inherently dynamic behaviour. Abstract : Synthetic supramolecular chemistry pursues not only the construction of new matter, but also control over its inherently dynamic behaviour. In this context, classic host–guest chemistry, based on the development of a myriad of macrocyclic receptors with fine-tuned affinities and selectivities, has enormously contributed to the discovery of new chemical function under self-assembly conditions. In turn, the use of molecular switches as control units within host–guest assemblies opened the door for the regulation of their dynamic interactional behaviour, which can be translated into controlled aggregation. In this review, we will focus on different strategies developed for the regulated binding of organic molecules by switchable macrocyclic hosts. As we will see, an appropriate design using stimuli-responsive versions of well-known organic receptors allows the molecular switches implemented within their structures to transform their regulated behaviour from the molecular to the supramolecular level.